MULTIMEDIA LEARNING IMPLEMENTATION AND VOCABULARY MASTERY FOR ENHANCHING STUDENTS’ JAPANESE LANGUAGE READING SKILL AT SMKN 1 PURWOKERTO - Haryono Haryono (IZUMI, 2014)
The present research is the implementation of the 2013 doctoral disertation report funded by DIKTI. The research is a part of IPTEKS scheme for community devotion that have strong relation to language education technology. It concern with the use of multimedia learning and vocabulary mastery on students’ Japanese language  reading skills at SMK 1 Purwokerto. The method is implemented experimentally by giving multimedia learning treatment such as Rosetta Stone and Tell Me More Japanese. Through some presentation with the use of those multimedia learning material, the purpose of this research is to know the extent to which the level of their vocabulary mastery and to encourage students in order to have an approriate skill to read Japanese documents. With the implementation of this multimedia learning training, graduate students of SMK Negeri I Purwokerto will be increased and for the future they have a good job at Japanese companies in Indonesia